Formation of nuclear condensates by the Mediator complex subunit Med15 in mammalian cells - Yuanyuan Shi (BMC, 2021)
Abstract Background The Mediator complex is an evolutionarily conserved multi-subunit protein complex that plays major roles in transcriptional activation and is essential for cell growth, proliferation, and differentiation. Recent studies revealed that some Mediator subunits formed nuclear condensates that may facilitate enhancer-promoter interactions and gene activation. The assembly, regulation, and functions of these nuclear condensates remain to be further understood. Results We found that Med15, a subunit in the tail module of the Mediator complex, formed nuclear condensates through a novel mechanism. Nuclear foci of Med15 were detected by both immunostaining of endogenous proteins and live cell imaging. Like Med1 foci and many other biomolecular condensates, Med15 foci were sensitive to 1, 6-Hexanediol and showed rapid recovery during fluorescence recovery after photobleaching. Interestingly, overexpressing DYRK3, a dual-specificity kinase that controls the phase transition of membraneless organelles, appeared to disrupt Med1 foci and Med15 foci. We identified two regions that are required to form Med15 nuclear condensates: the glutamine-rich intrinsically disordered region (IDR) and a short downstream hydrophobic motif. The optodroplet assay revealed that both the IDR and the C-terminal region of Med15 contributed to intracellular phase separation. Conclusions We identified that the Mediator complex subunit Med15 formed nuclear condensates and characterized their features in living cells. Our work suggests that Med15 plays a role in the assembly of transcription coactivator condensates in the nucleus and identifies Med15 regions that contribute to phase separation.